2015
DOI: 10.7567/jjap.54.04dr04
|View full text |Cite
|
Sign up to set email alerts
|

Degradation by acetic acid for crystalline Si photovoltaic modules

Abstract: Degradation by acetic acid for crystalline Si photovoltaic modules during damp-heat test was analyzed by observing electrical and electroluminescence properties. Change in electroluminescence images is explained based on corrosion of electrodes by acetic acid. Difference in the pattern of the dark region in electroluminescence image is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 37 publications
4
56
0
Order By: Relevance
“…10) However, the relationship between the DH test and the real exposure test has not been completely understood, and precise determination of the acceleration coefficient of the DH test is still challenging. 8) Much effort has been dedicated to clarifying the degradation mechanism of a PV module during the DH test, 6,9,10) and recent studies have revealed that the production of acetic acid from the ethylene-vinyl acetate (EVA) copolymer encapsulant is one of the serious causes of degradation. 6,[11][12][13] The production pathway of acetic acid during the DH test is considered to be the hydrolysis of the EVA encapsulant by water from moisture penetrating into the back sheet of a PV module.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10) However, the relationship between the DH test and the real exposure test has not been completely understood, and precise determination of the acceleration coefficient of the DH test is still challenging. 8) Much effort has been dedicated to clarifying the degradation mechanism of a PV module during the DH test, 6,9,10) and recent studies have revealed that the production of acetic acid from the ethylene-vinyl acetate (EVA) copolymer encapsulant is one of the serious causes of degradation. 6,[11][12][13] The production pathway of acetic acid during the DH test is considered to be the hydrolysis of the EVA encapsulant by water from moisture penetrating into the back sheet of a PV module.…”
Section: Introductionmentioning
confidence: 99%
“…8) Much effort has been dedicated to clarifying the degradation mechanism of a PV module during the DH test, 6,9,10) and recent studies have revealed that the production of acetic acid from the ethylene-vinyl acetate (EVA) copolymer encapsulant is one of the serious causes of degradation. 6,[11][12][13] The production pathway of acetic acid during the DH test is considered to be the hydrolysis of the EVA encapsulant by water from moisture penetrating into the back sheet of a PV module. 13,14) Then, the generated acetic acid attacks not the pn junction 6,15,16) but the interface layer between the Ag finger electrodes and the Si emitter layers through the corrosion of lead compounds contained in a screen-printed Ag paste, resulting in the increase in contact resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the increase in R s is derived from the increase in contact resistance between the Ag finger electrode and the Si cell due to the production of acetic acid gas by the hydrolysis reaction of EVA. 13) Since the water vapor permeability of the backsheet used in this study is equivalent to that of the poly(vinyl fluoride) (PVF)=PET=PVF backsheet used in Masuda et al's study 25) and a similar EVA to that used in their report is used as the encapsulant, the durability of modules using bifacial cells and monofacial cells can be compared. Generally, a monofacial p-type Si cell includes an Al back surface field (BSF) on the whole rear surface.…”
Section: Resultsmentioning
confidence: 99%
“…We do not discuss the initial degradation and yearly degradation rates of performance in this paper. The degradation of front contact characteristics, which leads to an increase in series resistance, [11][12][13][14] and potentialinduced degradation (PID), which leads to a decrease in shunt resistance, [15][16][17] significantly affect the module lifetime. In this paper, some aspects of mechanism analyses of these degradation modes are described and the comparative experimental test results of the samples fabricated using conventional technology or our technology are also described.…”
Section: Introductionmentioning
confidence: 99%